Vibroacoustic analysis of a simply supported rectangular plate of a power transformer casing - Rdzanek, W. P.; Zawieska, W. M. (Archives of Acoustics, 2003)
This paper deals with some vibroacoustic processes occuring within the power transformer casing. The acoustic system is modeled by a simply supported rectangular plate embedded within the planar rigid baffle. The radiation directivity pattern of the system is specially focused on since it will be useful for the determination of the eigenfunctions of the system; the latters are necessary for some further analysis of the total sound power radiated by the system and the resultant distribution of the sound pressure radiated as well as for some further investigations on the noise control of the system.